Invasive common milkweed strongly simplifies insect flower-visiting networks - Edina Török; Riho Marja; Ágota Réka Szabó; Róbert Gallé; Péter Batáry (Basic and Applied Ecology)
Plant invasion and habitat fragmentation are significant global drivers threatening biodiversity. Synergistic interactions between these processes can lead to even more significant biodiversity loss than when they act alone. However, their effects on flower visiting insects and their food resources are complex and lack a general consensus. In this two-year study, we analysed the structural changes in plant-flower visitor networks in response to the interaction between common milkweed (Asclepias syriaca) invasion and fragment size. We selected natural forest-steppe grassland fragments along a gradient of fragment sizes in Hungary by designating invaded and control areas in each to survey flower visitors and their food plants before and during milkweed flowering. We found that Shannon diversity and generality of networks were significantly lower in milkweed-invaded areas compared to control areas during milkweed flowering. More diverse networks were observed in the control areas. Functional complementarity and the cluster coefficient of networks were significantly higher in milkweed-invaded areas compared to control areas during milkweed flowering. However, we found no effect of fragment size. Our results showed that during its flowering period, milkweed significantly impacted and simplified flower-visiting insect networks. The flowers of the invasive milkweed attracted flower visitors with suitably long tongues, potentially disrupting local flower-visiting species. Our research highlights that exploring networks provides valuable insights into the indirect consequences of plant invasion and offers new knowledge for habitat restoration efforts.